Moving to Collective Efficacy: How Inner-City Mobility Impacts Minority and Immigrant Youth Victimization and Violence, Chicago, Illinois, 1994-2002 - Antunes, Maria João Lobo ([Verlag nicht ermittelbar], 2020)
Despite much recent attention devoted to understanding the ramifications of residential mobility, especially negative consequences for youth, there is scant research exploring how inner-city mobility impacts youth violence and victimization among minorities and immigrants. Leaving the city imparts benefits: decreasing deviance and improving youth outcomes. Considering that many are unable to "escape" the city, clarifying what effects, if any, inner-city mobility has is critical. Destination neighborhoods for youth who move in the city are either contextually the same, better, or worse than their original neighborhood. Evidence suggests that immigrant families are more likely to move as are racial minorities. Because of this, the researchers examined the extent to which moving within a city affects minority and immigrant youth experiences, particularly in relation to changes in neighborhood collective efficacy; a major characteristic shaping community crime rates and youth violence. This project involved four main goals: identify key characteristics of the destination neighborhoods and those who are moving within the city of Chicago; understand how inner-city mobility of minority and immigrant youth affects engagement in violence and victimization; determine whether vertical or horizontal mobility with respect to key neighborhood factors differentially influences minority and immigrant youth outcomes; assess who fares better - youth who vertically move (to better or worse neighborhoods), those who do not move, or those who horizontally move (to equivalent neighborhoods). This research used data from the Project on Human Development in Chicago Neighborhoods (PHDCN). Data were drawn from both the Longitudinal Cohort Study (N=1,611) and Community Survey (N=97). The rich data from the Community Survey affords the opportunity to examine how community characteristics like collective efficacy, disorder, and indicators of social disorganization can impact a variety of youth behaviors among at-risk youth over time between Wave 1 and Wave 2 and Wave 2 and Wave 3. The Longitudinal Cohort Study provides data on youth characteristics and experiences with violence, and ecological information on family and peer relationships. The investigators focused primarily on three of the seven youth cohorts from the Longitudinal Cohort Study: 9, 12, and 15. The ages of these youth during the study period place them at increased risk for exposure to community violence, and place them in range for aging into, peaking, or aging out of crime and delinquency. The Longitudinal Cohort Study respondents are nested in neighborhood clusters and multilevel models are employed to assess the outcomes victimization and violence within neighborhood context. The researchers employed a series of hierarchical generalized linear models using HLM 7 in addition to running several analyses of variance (ANOVA) permitting examinations between groups of interest.